Glutathione gel-encapsulated niosomal delivery system versus glutathione gel only in treatment of melasma: a comparative study - Eman S. Abdel-Azim; Usama F. Aly; Heba O. Dakhly; Mahmoud H.A. Montaser (Journal of the Egyptian Women’s Dermatologic Society)
Background Glutathione is an antioxidant agent used in the treatment of melasma. However, niosome is a drug delivery enhancer used in other skin diseases to increase the absorption of any active ingredient. Objective To assess the efficacy of niosome with topical glutathione gel 2% in the treatment of melasma versus topical glutathione gel 2% alone. Patients and methods In this comparative study, 19 patients complaining of melasma were divided into two groups. Group 1 was treated with glutathione gel 2% only, while group 2 was treated with glutathione gel 2% encapsulated in niosome. The split face method was used where right side of face for treatment and left side for placebo. Patients were photographed and examined clinically by Wood’s light and dermoscopy. All patients were evaluated clinically using a modified Hemi-Melasma Area and Severity Index (HEMI-MASI) score with the calculation of the reduction percentage and grading of the improvement. Moreover, histopathological examination was done before and after treatment. Results In Glutathione treated right side, hemi-MASI score after treatment was decreased with no significant difference when compared with base line; while in Glutathione gel with niosome treated right side; hemi-MASI score was significantly decreased. There was a high significant difference in reduction percentage of hemi-MASI score of both right sides of face of the two groups. No side effects were reported by patients of both groups. After treatment, both H and E and FM sections showed a decrease in basal hyperpigmentation in the case of epidermal melasma and a decrease in dermal melanophages in mixed melasma in both groups. Conclusion Topical glutathione gel alone without niosome is a weak melasma treatment. Niosome enhances glutathione gel absorption and efficacy without any side effects.